Unveiling the intricacies of bone homeostasis: Epigenetic regulation, extracellular vesicles, and angiogenesis integration - Célio Junior da Costa Fernandes (Extracellular Vesicle)
Bone homeostasis is a complex process involving the coordinated actions of various bone cells and their interactions with the surrounding microenvironment. Epigenetic regulation, specifically through DNA methylation, histone acetylation, microRNAs, and long non-coding RNAs, has been identified as a crucial factor in maintaining bone health. Furthermore, the interplay between bone cells and angiogenesis, the process of forming new blood vessels, plays a critical role in maintaining bone health. Epigenetic factors have been found to regulate angiogenesis in bone tissue. Extracellular vesicles derived from different cell types, such as osteoblasts, endothelial cells, and mesenchymal stem cells, are also important in bone homeostasis. These vesicles transport bioactive molecules, including microRNAs, growth factors, and cytokines, which regulate angiogenesis and influence the function of bone cells. Understanding the epigenetic control of gene expression and the role of extracellular vesicles in bone homeostasis has significant implications for the development of therapeutic strategies for bone disorders. This knowledge is particularly valuable in the context of aging, metabolic disorders, and pathological disruptions of bone homeostasis.